Compound Odontoma Associated with Dentigerous Cyst Incidentally Detected in an Adult Patient: Tomography and Histological Features. (2nd May 2022) - Manfredini, Mattia; Ferrario, Susanna; Creminelli, Luca; Kuhn, Elisabetta; Poli, Pier Paolo
Abstract : Odontoma is the most common benign odontogenic tumor of epithelial and mesenchymal origin. The standard treatment involves a conservative approach. While this procedure is generally well accepted and tolerated, some difficulties may arise in case of odontomas associated with cystic lesions. In general, the expansive nature of cystic lesions requires their surgical excision, different from isolated nonsymptomatic odontomas that can be monitored radiographically. However, to the best of our knowledge, there is scarce evidence currently available reporting on the presence of odontoma-associated cystic lesions in the oral cavity. Therefore, the present case report is aimed at describing the diagnostic clinical, radiological, and histological features together with the surgical management of a dentigerous cyst associated with a compound odontoma. Following surgical removal of the lesion, no recurrence was observed after 12 months of follow-up.